A study on primary caesarean section at tertiary care hospital - Gori, Mahejbin I.; Akhani, Riddhi; Patal, Mosam R.; Bhatt, Jalpa K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Caesarean section represents the most significant operative intervention in obstetrics and its development and application has saved the lives of countless mothers and infants. However, there has been a steady increase in the rate of caesarean sections worldwide. In this study, we aim to find the primary caesarean section rates and strategies to cut it down. Methods: A retrospective study was conducted at SMS Multispecialty Hospital and Dr. M. K. Shah Medical College and Research Centre from November 2022 to April 2023.The study include all the patients for primary caesarean section those patient have previous cesarean section were excluded. Results: In this study the rate of primary caesarean section was found to be 14.5% and the majority of the study subjects belonged to the age group of 18-27 years (91.4%). With respect to parity, primigravida were high in number (85%), followed by multigravida. The number of emergency caesarean sections were (79%) more than elective (21%). The most common intra-operative complication was post-partum haemorrhage (PPH) in 8.5% and the most common postoperative complication was wound gape in 8.5%. Conclusions: Maximum efforts should be made to allow progression of vaginal delivery in primigravida which helps us to bring down the primary caesarean rate.